THE EFFECTIVENESS OF THE ICE BREAKING METHOD ON MOTIVATION TO LEARN GRAMMAR - Sherly Yustuti; Masrun Masrun; Agustiar Agustiar; Fathah Rizki Mubina (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research aims to determine the effectiveness of the ice breaking method on the motivation to learn grammar among first-year female students at the Intermediate School of Muhammadiyah Teacher Training Institute, Bangkinang Kota, Kampar District. The research questions are: